2005
DOI: 10.1038/modpathol.3800456
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 5/14-positive breast cancer: true basal phenotype confined to BRCA1 tumors

Abstract: Breast ducts contain two types of epithelial cells, inner luminal cells and outer basal/myoepithelial cells. These cells can be distinguished by their immunophenotype. Cytokeratins (CKs) 8 and 18 are expressed in the luminal layer, whereas CK5/14 and the transcription factor p63 characterize the basal epithelial layer. We studied a population-based cohort of 288 sporadic ductal invasive cancers and found 9% positive for CK5/14 and 4% positive for p63. Using a highly sensitive polymer-based immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
140
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(161 citation statements)
references
References 33 publications
(80 reference statements)
10
140
1
5
Order By: Relevance
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 57%
“…This was performed simply to increase the yield of high-grade, ER-negative breast carcinomas, as these are more common in the younger age group. The majority of BRCA-1-associated tumors have the basal phenotype, 8,18,19 but the BRCA-1 status was not available for any of our cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue microarrays containing formalin-fixed paraffin-embedded tissues in replicates from 425 individuals diagnosed with stage II invasive breast cancer but without a significant family history of breast or ovarian cancer were subjected to IHC staining for CK5/14. CK5/14 IHC was performed and scored into CK5/14-positive (defining basal-like status) and CK5/14-negative groups as described 17 . Some of these individuals were evaluated for PTEN protein expression by IHC on whole-mount, formalin-fixed, paraffin-embedded tissue sections, and the tumors were scored as PTEN-positive (PTEN IHC-positive ) or PTEN-loss (PTEN IHC-loss ) relative to normal epithelial, endothelial and/or stromal cells in each tissue section as described 15 .…”
Section: Human Tumor Samples and Immunohistochemistrymentioning
confidence: 99%
“…Sie machen 2-18% al ler invasiven Mammakarzinome aus und sind durch einen hohen Malignitätsgrad, das Fehlen von Hormonrezeptoren und HER2/neu, einer häufigen EGFR ("epi dermal growth factor receptor ")Über expression sowie immunphänotypischen Merkmalen basaler bzw. myoepithelialer Brustepithelzellen charakterisiert [7,10,16,19,22]. BLBCs stellen den häufigsten Subtyp bei BRCA1 assoziierten Mamma karzinomen dar [20].…”
Section: Diskussionunclassified